The Relations Among Types of Parentification, School Achievement, and Quality of Life in Early Adolescence: An Exploratory Study - Borchet, Judyta; Lewandowska-Walter, Aleksandra; Połomski, Piotr; Peplińska, Aleksandra; Hooper, Lisa M. (Frontiers in Psychology, 2021)
Children who experience parentification may have trouble performing developmental tasks due to being overwhelmed with their family caregiving roles and responsibilities. Past studies have found that parentification is negatively associated with academic achievement. However, most of these studies are limited in that they are retrospective and examine the association but not the mechanisms shaping them. The aim of the study was to explore to what extent diverse types of parentification relate to academic achievement and to what extent these relations are mediated by self-reported quality of life among adolescents. The study sample was comprised of Polish early adolescents (N = 191; age: M = 14.61; SD = 1.26). Types of parentification were measured with the Parentification Questionnaire for Youth and quality of life was assessed with KidScreen27. School achievement was measured based on mean semester grade. We explored the associations among study variables and performed six mediation models in the planned analyses. Overall, bivariate relations were significant in theoretically expected way, although the effect sizes for these associations were rather small. In the mediation analyses, the results showed four of the six models were not significant. Different than previous studies, instrumental parentification was positively related with school achievement. Additionally, this positive association was mediated by adolescent’s general quality of life. Taken together, the findings were similar and different than the empirical literature base on types of parentification and select outcomes.